Touching, unbelonging, and the absence of affect - Khanna, Ranjana (Feminist Theory, 2012)
This article argues that psychoanalytic notions of affect – including ideas of anxiety and melancholia, as well as deconstructive concepts of auto-affection – offer a feminist ethico-politics and a notion of affect as interface. Beyond the confines of the experiential and the positivist, both psychoanalysis and deconstruction provide insights into affect as a technology that understands the subject as porous. I consider works by Derek Jarman and Shirin Neshat to demonstrate the importance of the ethico-politics of affect as interface in contemporary cultural production. Both artists, in the process of considering the spectacular nature of notions of feminist and queer, use images of interface as a way of delimiting the spectacular nature of being and demonstrating the singularity of the event, the desire to fix through framing, and the parergonal nature of framing. The presence of the subject is questioned even as an auto-affection is suggestive of a spectral demand of the ethico-political. In the case of Jarman’s Blue, the denial of image as face in favour of the screen as interface is interrupted by sound and voice, which gesture toward representation as impossible but necessary. In the case of Neshat, the persistence of the photographic – the highly aesthetic self-portrait as mugshot – foregrounds face as interface, as one that questions presence through the insistence of a representational apparatus.
Keywords: approches et analyses; arts; arts visuels et médiatiques; discipline; photographie; psychanalyse; psychoanalyse; queer; ressource en ligne; émotions

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communications; discipline; fem1000; premier cycle; psychanalyse; queer; régions géographiques; thématiques; violences; états-unis; études culturelles